Length-based Assessment of Jinga shrimp (Metapenaeus affinis) in CilacapWaters, Indonesia: Length-based Assessment of Jinga shrimp (Metapenaeus affinis) in Cilacap waters, Indonesia - Harlyan, Ledhyane Ika; Zulfania, Herlian Putri; Bintoro, Gatut (Journal of Tropical Life Science, 2026)
Cilacap Regency, Central Java, is a major fishing hub, and tropical shrimp, including Jinga shrimp (Metapenaeus affinis), are among the most valuable resources due to their high demand and economic importance. However, penaeid shrimp stocks in the Indonesian Fisheries Management Area (FMA) 573, including Cilacap waters, are reported to be overexploited. This study aims to assess the stock status of Metapenaeus affinis in Cilacap waters using length-based stock assessment methods, including the Length-Based Spawning Potential Ratio (LB-SPR) approach, to evaluate exploitation status relative to biological reference points. Sampling was conducted from December 2024 to March 2025, yielding 2,099 individuals collected from the Tegalkamulyan landing site. Biological parameters, including carapace length, body weight, sex, and gonad maturity stage, were analyzed. The results showed a negative allometric growth pattern (b = 1.5887). The length at first capture (Lc = 34.8 mm CL) was lower than the length at first maturity (L50 = 40.8 mm CL), indicating that most individuals are harvested before reproducing. The estimated spawning potential ratio (SPR) was 6%, confirming severe overexploitation. These findings highlight the urgent need for management measures, such as minimum size limits, improved gear selectivity, and seasonal closures, to ensure sustainable use of shrimp resources in Cilacap waters.